Actinomyces bouchesdurhonensis sp. nov. and Actinomyces mediterranea sp. nov., isolated from human stomach and duodenum. (March 2017) - Mailhe, Morgane; Ricaboni, Davide; Benezech, Alban; Cadoret, Frédéric; Fournier, Pierre-Edouard; Raoult, Didier
Abstract: We propose here the main characteristics of the new bacteria Actinomyces bouchesdurhonensis strain Marseille-P2825 (CSUR P2825) isolated from a gastric liquid sample of a 60-year-old man and Actinomyces mediterranea strain Marseille-P3257 (CSUR P3257) isolated from a duodenal liquid sample of a 76-year-old woman.